Community Conceptions and Perceptions of Climate Change Mitigation and Adaptation in Ternate - Abbas, Sukardi; Sahjad, Sumarni; Syawal, Julkarnain; Amin, Astuti Muh.; Nurbaya, Nurbaya (Journal of Community Based Environmental Engineering and Management, 2023)
The community's input on climate change issues in the city of Ternate is urgently needed. The purpose of this study is to document how the people of Ternate City understand and respond to issues of climate change mitigation and conditions. This study used a community-based participatory research method involving 30 people consisting of community members, teachers, lecturers, and students. Focus group discussions (FGD) and photovoices were conducted to obtain data on causes, impacts and solutions to climate change problems in the city of Ternate. The research results confirmed that the people in the city of Ternate feel the negative impacts of climate change in the city, such as reduced water sources, loss of plant vegetation (for example: mangroves, sago and sea grass), reduced marine habitats, floods and landslides at several points, increased sea level. The main causes of climate change in the city of Ternate are the establishment of non-environmentally friendly development policies, the lack of public knowledge and awareness of climate change adaptation, and the lack of regional regulations at the city to village levels related to environmental issues. The solutions offered by the community are very diverse but according to the community, the government and young people need to conduct education, mitigation, and adaptation to climate changes in the city of Ternate.